Risk of tuberculosis in children with rheumatologic diseases treated with biological agents: A cross-sectional cohort study - Nuri Bayram,; Özge Altuğ Gücenmez,; Balahan Makay,; Elif Kıymet,; Elif Böncüoğlu,; Şahika Şahinkaya,; Yelda Sorguç,; Aybüke Akaslan Kara,; Kamile Ötiken Arıkan,; İlker Devrim, (Archives of Rheumatology, 2023)
Objectives: This study aimed to evaluate the risk of tuberculosis (TB) disease in children receiving biological agents for rheumatologic diseases, focusing on appropriate screening tests in a high-priority country for TB control. Patients and methods: One hundred nine children (56 females, 53 males; range, 3.4 to 16.2 years) who received any biological agent for rheumatologic diseases for more than two years between May 2012 and October 2021 were included in this retrospective study. Patients were screened for TB infection using tuberculin skin test (TST) or interferon-gamma release assay (IGRA). Following the initial evaluation, patients were clinically examined for TB every three months by a comprehensive medical history and physical examination, and every 12 months using TST or IGRA. Results: At the initiation of the biological agent, the patients’ mean age was 12.4±4.5 years. The average follow-up duration was 3.6±1.3 years (range, 2.6 to 10.2 years) for patients treated with biological agents. Each patient had a documented Bacillus Calmette-Guérin vaccination. Before the initiating of therapy, TST was performed alone in 45 (41.3%) patients and in combination with IGRA in 64 (58.7%) patients. In the 64 patients who underwent both TST and IGRA, IGRA revealed nine (14.1%) positive results. Six (66.7%) of these nine patients, however, had negative baseline TST. Four (7.3%) of the 55 individuals whose initial IGRA results were negative also had positive TST results. Overall, no TB disease was observed after a follow-up period. Conclusion: This study reveals that biological agents were not associated with an increased risk of TB disease in closely monitored children. Additionally, the concomitant use of TST and IGRA for screening of TB is reasonable in patients receiving biological agents.